Republic of Mozambique : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
Mozambique's strong macroeconomic performance continued in 2005 and early 2006, despite exogenous shocks. Fiscal results were commendable, and all performance criteria through end-March 2006 were met. Although the macroeconomic outlook remains favorable, vigilance will be required, in light of volatile oil prices and unpredictable weather. The main challenges are sustaining broad-based economic growth and making further inroads in alleviating poverty through the implementation of a poverty reduction strategy for 2006-09. The authorities' commitment to create sufficient fiscal space for priority investments is welcomed.